Pemanfaatan Liveworksheets dalam Pengembangan E-LKPD Numerasi Berbasis Ke-Islaman untuk Melatih Kemampuan Berpikir Tingkat Tinggi - Yanti, Aning Wida; Sutini; Putri, Alfina Rifky Taftiana (Circle: Jurnal Pendidikan Matematika, 2024)
This study aims to develop E-LKPD based on Numeracy Literacy Integrated with Islamic content with the help of liveworksheets to train students' critical thinking skills. The type of research is development research. The development procedure uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The product developed is E-LKPD—number and Algebra Material. Based on the research results, it was found that (1) The E-LKPD development procedure uses the ADDIE Development Model, whereas, in the Analysis Stage, data was obtained that the use of learning media was still less than optimal, especially for materials considered difficult by students. In the Design Stage, an E-LKPD design was produced. In the development stage, E-LKPD was developed, validated, and revised based on input from the validator. In the implementation stage, the process of implementing E-LKPD for students was carried out. In the Evaluation Stage, an assessment of the effectiveness of E-LKPD was carried out; (2) The E-LKPD developed meets the criteria of "Very valid" where the average total validity obtained is 4.60 and the average total practicality value obtained is 91.73 (criterion A). While in the practical aspect for the average student response questionnaire 99.21% (Very good category). The developed E-LKPD meets the criteria of "Effective" for training students' critical thinking skills (based on the results of the Critical Thinking Skills Test, Interpretation was 81.25% (Good), Analysis 84.82% (Very Good), Inference 79.46% (Good), Evaluation 75.00% (Good), Explanation 70.54% (Good), and Self-regulation 68.75% (Good)).